Extended-Spectrum β-Lactamase Producing Escherichia coli in Stray Cats from Northern Italy. (March 2022) - Ratti, G.; Stranieri, A.; Penati, M.; Dall'ara, P.; Luzzago, C.; Lauzi, S.
Abstract : Purpose: The incidence of infections with Extended-spectrum β-lactamase (ESBL) producing Escherichia coli ( E. coli ) is increasing and represents a threat to human and animal health. Pet animals have been reported as potential carriers of clinically important multi-drug-resistant E. coli but information on the role of stray cats is limited. The aim of this study was to determine the prevalence of ESBL producing E. coli in cats living in colonies from Northern Italy. Methods & Materials: Stray cats admitted to the Veterinary Teaching Hospital of Lodi, University of Milan, only for mandatory sterilization programs were sampled in 2020. Rectal swabs collected from each cat were enriched and cultured on solid chromogenic selective media. Species identification of phenotypically ESBL-producing isolates was accomplished via matrix-assisted laser desorption/ionization-time-of-flight mass spectrometry (MALDI-TOF MS) using the direct transfer method. Polymerase Chain Reaction (PCR) was used to detect bla CTX-M, bla SHV and bla TEM gene codes and isolates were divided into different phylogenetic groups. Isolates of ESBL-producing E. coli were subjected to antimicrobial susceptibility testing using minimum inhibitory concentration (MIC) determination. Results: A total of 79 cats from 12 colonies were screened. Four (5.1%) stray cats from three different cat colonies were found positive for ESBL-producing E. coli . The ESBL-producing E. coli isolates exhibited a multidrug-resistant phenotype, with all isolates resistant to ampicillin, cefazolin, cefovecin, cefpodoxime, cephalexin and tetracycline. In the multidrug-resistant E. coli, the PCR results showed that bla CTX-M was the predominant ESBL gene identified with all four isolates carrying the bla(CTX-M-1)-group β-lactamase genes, followed by bla TEM which was found in three isolates, whereas bla SHV was not detected. Three of the ESBL-positive E. coli isolates belonged to commensal groups (A; B1), whereas one isolate belonged to the B2 phylogroup Conclusion: Our results provide important baseline information on the carriage of multidrug-resistant E. coli among stray cats. Considering that the presence of antimicrobial selection pressure is unlikely or represents sporadic events in cat colonies, our results also suggest that stray cats may be sentinels for ESBL-producing E. coli circulation. Further studies using a One Health approach are needed to understand the drivers of antimicrobial resistance at the human-animal-environmental interface.